Fully-Additive Printed Electronics: Transistor model, process variation and fundamental circuit designs - Zhang, Xi (2015)
Printed Electronics (PE) on flexible substrates (e.g. plastic-film) is an emerging technology that potentially complements silicon-based electronics. To facilitate the design and realization of PE analog and digital circuits for the augmentation of signal processing thereto, we present in this paper, a novel and comprehensive printed transistor model that is simple, accurate and compatible with industry-standard IC (integrated circuit) electronic design automation tools. Unlike reported models, the proposed comprehensive model accommodates and accurately models the effect of the channel length on carrier mobility, leakage current and parasitic capacitances, and is valid for all transistor operating regions, from cut-off to supra-threshold regions. The proposed comprehensive model further embodies process variations (statistical data) and matching based on various layout techniques. These comprehensive modelings are imperative for the practical design and simulation of PE circuits, including manufacturability and implications with respect to the challenges of PE circuits.